Dynamics of a Tidal Current System in a Marginal Sea: A Case Study of the Yellow Sea, China - Zhang, Qian; Su, Min; Yao, Peng; Chen, Yongping; Stive, Marcel J. F.; Wang, Zheng B. (Frontiers in Marine Science, 2020)
Tidal current is one of the main driving forces for shaping the topography of marginal seas. A globally unique radial sand ridge field exists in the South Yellow Sea off the central Jiangsu coast, China. Its formation is related to the distinctive ‘radial tidal current’ pattern at that location. A generally accepted hypothesis is that the ‘radial tidal current’ is a consequence of the interaction between the northern amphidromic tidal wave system and the southern incoming tidal wave. In this study, we adopted a schematized numerical tidal model to directly investigate the tidal current system and the factors of influence in the South Yellow Sea. We first introduce the tidal Current Amphidromic Point (CAP) and the tidal current inclination angle for illustration of a tidal current system. By conducting series of numerical experiments, we found that the overall basin aspect ratio and the cross-basin phase differences of the tidal wave are two aspects of influence on the emergence of the ‘radial tidal current’. The ‘radial tidal current’ has opportunities to emerge in a basin where the basin length (L) is larger than width (B), and a lateral depth difference exists (or the offshore incoming tidal wave has an oblique angle). The Yellow Sea is featured by these aforementioned prerequisites favouring the formation of the ‘radial tidal current’. Further results analyses indicate that the CAP system (i.e., the co-inclination lines, the CAPs and the tidal ellipticity) can get deeper insights into the dynamic structure of a tidal current system than the tidal ellipse field and therefore it deserves more attention in future study.